School Influences on the Values Development of Grade School Learners (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
The myopic view of education centers on the holistic development of a child. As such, society expects schools to render training and education of the whole person. Schools exist to carry out the mandate of the state of preparing its citizens, particularly children, for the future ahead of them by providing academic training that promotes personal development rooted in social responsiveness. Thus, this study determined school determinants to the development of the intermediate pupils of Vineyard Christian Academy during the school year 2018-2019 as a benchmark in the formulation of a pupil development program. The descriptive-correlation design was utilized, which involved the intermediate pupils, parents, and teachers of Vineyard Christian Academy. The researcher adopted a questionnaire as the main data gathering instrument of the study and used the mean, Pearson r, ANOVA, post hoc test (LSD), and regression analysis to treat the data statistically. The results revealed a laudable development of the character, personal responsibility, and academic well-being of the respondents as these are highly affected by people, processes, and places in the school. Meanwhile, the three groups of respondents significantly differ in their perceptions of the development of pupils and on the extent of effects of the different factors. Additionally, the areas of development of learners were significantly related to each other, while the people, school and the places in the school admirably predicted pupil development. The findings affirmed the results of earlier studies on the significant roles of the different school constituents in the development of learners. Hence, the researcher endorses the Pupil Development Program for adoption by Vineyard ChristianAcademy in the hope of contributing to the development of the value of the learners.
Keywords: school influences, values formation, pupil development program